IMPLEMENTASI PROGRAM PEMBERDAYAAN MASYARAKAT BERBASIS RUKUN WARGA (PMB-RW) DI KECAMATAN TENAYAN RAYA KOTA PEKANBARU TAHUN 2014-2019 - Azalea Yudhiake; Adlin " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
The Pekanbaru City Community Empowerment Program Based on Rukun Warga (PMB-RW) is a program that aims to improve the community's quality of life, both individually and in groups. The tridaya principle, which includes social, economic, and environmental empowerment, is a mechanism in the PMB-RW program's implementation. Since the beginning of the year of implementation, the budget for the PMB-RW program, which comes solely from the Pekanbaru City Budget, has caused problems in its implementation in Tenayan Raya District. In Tenayan Raya District, this results in limited facilities and a lack of public interest in participating in the PMB-RW program.            The goal of the study was to see how well the PMB-RW program was implemented in Tenayan Raya District, Pekanbaru City, using Donald S. Van Meter and Carl's six policy implementation indicators. E. Van Horn, such as policy standards and objectives, resources, inter-organizational relations, and implementing agent characteristics. , as well as the implementor's disposition, social, political, and economic conditions. The descriptive research method with a qualitative approach was employed in this study. Interviews, observation, and documentation studies were used to collect data. The problem investigated in this study is the implementation of the PMB-RW program in Tenayan Raya District from 2014 to 2019, as guided by the Regional Regulations and the Mayor Regulation of Pekanbaru City.            According to the result of this research, the PMB-RW program implementation in Tenayan Raya District from 2014 to 2019 did not go well. This is supported by six policy implementation indicators derived from interviews, observations, and documentation studies. The PMB-RW program's implementation in Tenayan Raya District failed to meet its goal of community welfare. The hope for the future is that the community's social, economic, and environmental well-being can be realized quickly.Keywords : Program Implementation, PMB-RW, Tenayan Raya District